2013
DOI: 10.1007/s40519-013-0083-2
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness mediates the relationship between emotion dysregulation and bulimia nervosa/binge eating disorder psychopathology in a clinical sample

Abstract: Emotion dysregulation has been linked to binge eating disorder (BED) and bulimia nervosa (BN) although the mechanisms by which it affects BN/BED psychopathology are unclear. This study tested loneliness as a mediator between emotion dysregulation and BN/BED psychopathology. A treatment-seeking sample of 107 women with BN or BED was assessed for loneliness (UCLA Loneliness Scale), emotion dysregulation (Difficulties in Emotion Regulation Scale), and BN/BED psychopathology (Eating Disorder Examination) before tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 24 publications
0
18
0
1
Order By: Relevance
“…In fact, solitude, in its aspects of the intimate, social, and affiliative components, has its most distressing effect if associated with difficulties in emotion regulation. Other studies have shown this strong association ( 69 ) and have investigated the role of emotion regulation strategies as a mediator of the sense loneliness perceived ( 70 ), whereas other authors have investigated loneliness itself as a mediator in the association between emotion regulation strategies and psychological outcomes ( 71 ), showing that loneliness mediates the association between the difficulties in regulating emotions and psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, solitude, in its aspects of the intimate, social, and affiliative components, has its most distressing effect if associated with difficulties in emotion regulation. Other studies have shown this strong association ( 69 ) and have investigated the role of emotion regulation strategies as a mediator of the sense loneliness perceived ( 70 ), whereas other authors have investigated loneliness itself as a mediator in the association between emotion regulation strategies and psychological outcomes ( 71 ), showing that loneliness mediates the association between the difficulties in regulating emotions and psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Irritability is a common symptom of depression, anxiety, PTSD, bipolar disorders, ADHD, and other mental disorders (American Psychiatric Association, ), but research on this emotion has been limited. Irritability has been studied in the context of emotion dysregulation, which is strongly associated with binge eating in the literature (Eichen et al, ; Kelly et al, ; Selby, Ward, & Joiner, ; Southward et al, ). Additionally, high levels of irritability may be explained by comorbid conditions such as anxiety and depression, as well as by continued restriction of food intake.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by experimental data showing that the suppression of negative emotions leads to increased food intake in both healthy normal weight students and obese individuals with and without binge eating disorder (BED; Evers et al, 2010 ; Svaldi et al, 2014 ). Importantly, negative emotions and their maladaptive regulation are considered key contributing factors to anorexia nervosa (AN; Harrison et al, 2009 ; Davies et al, 2012 ), bulimia nervosa (BN; Southward et al, 2013 ; Lavender et al, 2014 ), and BED (Vanderlinden et al, 2004 ; Brockmeyer et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%